Linking Lipid Metabolism to Chromatin Regulation in Aging. Issue 2 (February 2019) - Papsdorf, Katharina; Brunet, Anne
Abstract : The lifespan of an organism is strongly influenced by environmental factors (including diet) and by internal factors (notably reproductive status). Lipid metabolism is critical for adaptation to external conditions or reproduction. Interestingly, specific lipid profiles are associated with longevity, and increased uptake of certain lipids extends longevity in Caenorhabditis elegans and ameliorates disease phenotypes in humans. How lipids impact longevity, and how lipid metabolism is regulated during aging, is just beginning to be unraveled. This review describes recent advances in the regulation and role of lipids in longevity, focusing on the interaction between lipid metabolism and chromatin states in aging and age-related diseases. Highlights: The membrane lipids PE and PC decrease with age, whereas triglycerides generally increase. During aging, the fatty acid composition of membrane lipids shifts towards an increased PUFA to MUFA ratio. Long-lived organisms or mutants have a decreased PUFA to MUFA ratio or less unsaturated PUFAs, consistent with lower oxidation. Longevity interventions (e.g., dietary restriction) lower the triglyceride content in mice. Supplementation of specific MUFAs and PUFAs extends the lifespan of worms and improves age-related phenotypes in mammalian cells. Dietary lipids are used as a carbon source for histone acetylation and dietary short-chain fatty acids as a source for histone acylation. Metabolites such as SAM connect lipid metabolism to histone methylation.